Enhancing fluorescence in vivo imaging using inorganic nanoprobes. (August 2015) - Bouccara, S; Sitbon, G; Fragola, A; Loriette, V; Lequeux, N; Pons, T
Graphical abstract: Highlights: In vivo fluorescence imaging is increasingly used for biomedical applications. Inorganic nanoprobes present unique optical properties. NIR II emitting NPs enable higher resolution in deep tissues. Nonlinear excitation and time-gated detection lead to enhanced sensitivity. Multicomponent nanoprobes enable multimodal imaging. Abstract : Fluorescence imaging is a versatile tool for biological and preclinical studies with steady improvements in performance thanks to instrumentation and probe developments. The sensitive detection and imaging of deep targets in vivo is especially challenging due to the diffusion and absorption of light by the tissues and to the emission of autofluorescence from intrinsic chromophores. Fluorescent inorganic nanoparticles present interesting optical properties that may significantly differ from organic dyes. In this short review, we present recent developments in the design of these nanoprobes and their use for new in vivo fluorescence modalities which provide enhanced imaging capabilities.